PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK ELEKTRONIK (E-LKPD) BERBASIS HEYZINE FLIPBOOK MAKER UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA KELAS X DI SMA SWASTA FREE METHODIST MEDAN TAHUN AJARAN 2025/2026 - Siboro, Hotman; Revita Yuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the use of printed Student Worksheets (LKPD) in economics learning at Free Methodist Private Senior High School Medan, which were less attractive and had not optimally improved students’ learning outcomes. This study aimed to determine the feasibility, practicality, and effectiveness of an Electronic Student Worksheet (E-LKPD) assisted by the Heyzine Flipbook Maker application on the Financial Services Authority (OJK) topic. The study employed a Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were 36 tenth-grade students. The results showed that the developed E-LKPD achieved an average feasibility score of 94.03% (very feasible category) and a practicality score of 92.55% (very practical category). The effectiveness test indicated an increase in students’ average scores from 34.5 on the pre-test to 86.0 on the post-test. Furthermore, the Wilcoxon Signed Rank Test produced an Asymp. Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant difference between pre-test and post-test scores. Therefore, the Heyzine Flipbook Maker-assisted E-LKPD is feasible, practical, and effective for improving students’ learning outcomes in economics learning.